Meta-Analysis Effectiveness of Massage on Spasticity in Children with Cerebral Palsy - Muazarroh, Salma; Kristiyanto, Agus; Prasetya, Hanung (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: Children with spastic cerebral palsy generally experience spasticity in the upper and lower extremities. Spasticity is stiffness that occurs due to damage to the central nervous system caused during the child's growth and development from prenatal to postnatal. Spasticity can be controlled with intervention. The purpose of this study is to analyze, and estimate the effectiveness of massage for spasticity in children with cerebral palsy.Subjects and Method: This study uses a meta-analysis study design with PICO as follows: P= children with cerebral palsy, I= massage, C= non massage, O= Modified Ashworth Scale (MAS). The article search process was carried out between 2000-2020 using databases from PubMed, Google Scholar, PEDro, NCBI. Based on the database, there were 9 articles that met the inclusion criteria. This study involved 817 articles. The analysis was performed using Review Manager software (RevMan 5.3).Results A total of 9 Randomized Control Trial (RCT) studies from Europe, America, Asia and Africa were selected for systematic review and meta-analysis. COVID-19 patients receiving Ivermectin therapy decreased the duration of hospital stay by 1.52 units compared to standard therapy and this result was statistically significant (SMD= -1.52; 95% CI= -2.34 to -0.70; p= 0.003).Conclusion: Ivermectin can reduce the duration of hospital stay for COVID-19 patients.Keywords: Massage, cerebral palsy, Modified Ashworth Scale, meta analisisCorrespondence: Salma Muazarroh. Masters Program in Public Health. Universitas Sebelas Maret, Jl.Ir. Sutami 36A, Surakarta 57126, Jawa Tengah, Indonesia. Email: salma.azza@gmail.com. Mobile: 085642431178.Indonesian Journal of Medicine (2022), 07(02): 209-218https://doi.org/10.26911/theijmed.2022.07.02.09